Protein and carbohydrate fractionation of Piata palisadegrass silage of brans from biodiesel industry - Patrícia Soares Epifanio; Kátia Aparecida de Pinho Costa; Daniel Augusto Alves Teixeira; Patrick Bezerra Fernandes; Eliane Sayuri Miyagi Okada; Hugo Jayme Mathias Coelho Peron (Acta Scientiarum. Animal Sciences, 2014)
This study aimed to determine the protein and carbohydrate fractionation of Piata palisadegrass silage of brans from biodiesel industry. The experiment was developed in the Federal Institute of Goiás State, Campus Rio Verde, with a completely randomized experimental design, four replications, in a 4 x 4 factorial scheme, with four oleaginous brans (cotton, sunflower, soybean and canola) and four levels of inclusion (0, 5, 10 and 15%). The results showed that brans from biodiesel industry are good sources of additives for ensiling thePiata palisadegrass, by considerably improving fractions of proteins and carbohydrates. However, the soybean meal proved to be more efficient by having higher fractions of proteins and carbohydrates A+B1 and lower fractions C, compared with other additives. It is recommended the addition of 15% of brans for providing better nutritional value of silage.